ANALISIS BEARING PADA OUTPUT SHAFT GEAR REDUCER PUMPING MENGGUNAKAN SIMULASI ANSYS - Dwitama, Iksan; Hestiawan, Hendri; Winata, Alben Sindhu (UNIB Press, 2025)
Bearing is one of the main components in the gear reducer pumping unit that plays an important role in supporting the performance of the output shaft. In working conditions, this component receives high loads that can affect deformation, stress, and bearing life. This study was conducted at PT Bukaka Teknik Utama with the aim of analyzing the total deformation, Von Mises stress, safety factor, and bearing life using Ansys Workbench R1 2024 Student software simulation. The analysis was carried out by creating a bearing geometry design using SolidWorks 2024, determining AISI 52100 material, meshing, giving radial and axial loading, and static analysis simulation. Specific data, such as 32230 SKF bearing specifications and load values, were used to ensure the accuracy of the results. The results of the analysis showed a maximum deformation value of 0.17348 mm, a maximum Von Mises stress of 76.579 MPa, a minimum safety factor of 5.876, and an average bearing life of 1.057 x 1012 hours. From the analysis that has been done, the results obtained are that the bearing life is too large due to the limited mesh size and the small loading given so that the results obtained are inaccurate. The results of the analysis indicate that the bearing is in a safe condition to support the given load. This study recommends improving the quality of meshing in the simulation to obtain more accurate results.